Sistem Pakar Diagnosis Penyakit Hepatitis Menggunakan Metode Dempster Shafer - Ayu Tifany Novarina; Edy Santoso; Indriati Indriati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Hepatitis is an inflammation of the liver. Inflammation is characterized by elevated liver enzyme levels, due to liver membrane damage or damage. There are two factors that cause the factors of infection and non-infectious factors. There are 5 main hepatitis viruses, referred to as types A, B, C, D and E. These 5 types are of greatest concern because of the burden of illness and death they cause and the potential for outbreaks and epidemic spread.There are many other viruses that potentially cause hepatitis such as adenoviruses, herpes simplex, HIV, rubella, and others. The problems that often occur today is still a lot of ordinary people who lack understanding of health. In fact, not infrequently people do not realize when they get the disease because they do not know the symptoms that cause patients late to handle early. In this study the problems are solved by creating a system by implementing the Dempster-Shafer method to diagnose the types of hepatitis disease suffered by humans, so the system is expected to assist users in diagnosing hepatitis disease in misery since early. Based on the results of system accuracy testing with 20 data samples obtained an accuracy of 90%. Inaccuracy of 10% is caused by several things, among others, the subjectivity of the expert in determining the disease and in the calculations performed using the Dempster-shafer method that uses the highest value without any optimization of the density value on any symptoms.